Structural basis for mutually exclusive co-transcriptional nuclear cap-binding complexes with either NELF-E or ARS2 - Schulze, Wiebke Manuela; Cusack, Stephen (Nature Communications, 2017)
The nuclear cap-binding complex (CBC) binds to the 5′-cap structure of Pol II transcripts. Here, the authors give structural insights into CBC-mediated transcript processing and show that CBC forms mutual exclusive complexes with NELF and ARS2, which might act in earlier and later phases of transcription, respectively.